EFEKTIFITAS PROGRAM PENCIPTAAN 19 JUTA LAPANGAN KERJA TERHADAP PENURUNAN PENGANGGURAN (STUDI DATA BPS JAWA TIMUR). - Wira Yudha Alam; Muchammad Dava Ramahdan; Alfi Zidan; Nailah Hadyan Ramadhani; Yesika Fitri Aulia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Unemployment continues to be a significant macroeconomic challenge that impacts both economic stability and societal welfare. The government of Indonesia has launched a comprehensive policy aimed at generating 19 million job opportunities, bolstered by associated initiatives like the Free Nutritious Meal program, which has the potential to create jobs through the food supply sector and related industries. This research seeks to evaluate the success of the job creation initiative in lowering unemployment rates and to explore the function of the MBG program as a supplementary policy. The study utilizes a descriptive quantitative methodology, drawing from secondary information provided by the Statistics Indonesia for East Java Province, along with trend analysis and qualitative methods to evaluate indirect effects on employment. Findings suggest that job creation strategies generally aid in diminishing unemployment, though their success is affected by factors such as the quality of the labor force, the economic framework, and the distribution of jobs. The MBG initiative also demonstrates promise in generating new job prospects, but its execution needs enhancement to ensure wider and more lasting effects. ltimately, the job creation initiative is crucial in tackling unemployment, especially when reinforced by cohesive social policies, and harmonizing policies is vital to attain effective and sustainable employment results.